Impact of the COVID-19 Pandemic on Sexually Transmitted Infection Clinic Visits. Issue 1 (January 2021) - Tao, Jun; Napoleon, Siena C.; Maynard, Michaela A.; Almonte, Alexi; Silva, Elizabeth; Toma, Emily; Chu, Christina T.; Cormier, Kevin; Strong, Sabrina; Chan, Philip A.
Abstract : Abstract: Coronavirus disease 2019 is responsible for a global pandemic and has impacted health care accessibility and delivery. Clinic data were reviewed for an STI clinic from September 2019 to May 2020. A significant decrease in rates of STI visits and treatments during the coronavirus disease 2019 pandemic was observed. Abstract : During COVID-19 pandemic, access to services at a major sexually transmitted infections clinic significantly decreased. It is critical to implement novel approaches to maintain sexually transmitted infection services during COVID-19.